2022
DOI: 10.3349/ymj.2022.63.5.430
|View full text |Cite
|
Sign up to set email alerts
|

Severity-Adjusted Dexamethasone Dosing and Tocilizumab Combination for Severe COVID-19

Abstract: Purpose Real-world experience with tocilizumab in combination with dexamethasone in patients with severe coronavirus disease (COVID-19) needs to be investigated. Materials and Methods A retrospective cohort study was conducted to evaluate the effect of severity-adjusted dosing of dexamethasone in combination with tocilizumab for severe COVID-19 from August 2020 to August 2021. The primary endpoint was 30-day clinical recovery, which was defined as no oxygen requirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“… 12 This was recommended based on some randomized controlled studies in which its use, combined with dexamethasone, showed some benefit in terms of survival. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 This was recommended based on some randomized controlled studies in which its use, combined with dexamethasone, showed some benefit in terms of survival. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…12 This was recommended based on some randomized controlled studies in which its use, combined with dexamethasone, showed some benefit in terms of survival. 13,14 Our patient presented with risk factors in addition to immunosuppression due to diabetes, such as broad antibiotic use, hemofiltration procedures, and central venous and urinary catheters. 15 These factors altogether allowed the pulmonary invasion of the Trichosporon asahii.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab was more selectively prescribed in the patient whose oxygen demand suddenly increased. 34 Routine use of baricitinib or tocilizumab in severe patients was hampered by concern about additional immunosuppression to that by dexamethasone, although baricitinib or tocilizumab was used more frequently in an ICU.…”
Section: Clinical Experiences and Practices For Covid-19 Treatment In...mentioning
confidence: 99%
“…Сочетанная колонизация дыхательных путей микроорганизмами, одновременно преодолевающими эпителиальный барьер, может преоб-разовывать функции клеток иммунной системы, что способствует ускользанию этих патогенов от иммунного ответа. Остаются неясными особенности взаимодействия вируса SARS-CoV-2 с бактериями, разнообразие бактериально-вирусных взаимодействий при ко-инфицировании вызывает необходимость пересмотра подходов к их своевременному распознаванию и контролю, побуждает к созданию инноваций в биотехнологии и пересмотру стратегии борьбы с ко-инфицированием, развитию чего посвящены труды ученых во всем мире [9,10].…”
Section: Introductionunclassified